COMMUNITY RESILINECE IN A MOVING ISLAND OF SEKOPONG - Nazdan; Adi Asmariadi Budi (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
Sekopong Island, located on the eastern coast of East Lampung Regency, Lampung Province, Indonesia, is a unique island characterized by constantly shifting land. The island lacks vegetation, has sandy soil, and its terrain is continually reshaped by weather and wave conditions. Despite being unsuitable for permanent settlement, many people have built homes and continue to reside there. Economic opportunity serves as the main draw for settlers, particularly due to the island's rich crab fishing grounds. This study seeks to understand how the community on Sekopong Island adapts and remains resilient in the face of its extreme environmental conditions. A qualitative approach was employed to gather in-depth information from residents and relevant stakeholders. Data collection methods included community group discussions and in-depth interviews. Findings indicate that the primary reason for continued settlement is economic necessity. Most inhabitants are crab fishermen who rely on the island’s surrounding crab habitats for their livelihoods. The residents of Sekopong Island exhibit strong resilience in coping with the challenges posed by their dynamic and shifting environment.